STUDIES ON GROWTH CONDITIONS OF THE TOMATO ALTERNARIA LEAF SPOT CAUSING ALTERNARIA SOLANI L - JAGGAL SOMAPPA; K. SRIVASTAVA; B. K. SARMA; CHHATTAR PAL; RAVINDRA KUMAR (The Bioscan, 2013)
Alternaria leaf spot is the second most important disease of tomato after leaf curl virus causing severe loss every year. Studies of liquid media revealed that Alternaria solani growth was best on Potato Dextrose Broth (34.1mg) followed by Czapeck’s medium (58mm) and sporulation was maximum on Potato Dextrose Agar (13.2×106 spores/mL). The pathogen also sporulated maximum at temperature 25ºC and RH 100%.